Surface Structures and Electrochemical Activities of Pt Overlayers on Ir Nanoparticles - Lee, Kug-Seung; Yoo, Sung Jong; Ahn, Docheon; Jeon, Tae-Yeol; Choi, Kwang Hyun; Park, In-Su; Sung, Yung-Eun (AMER CHEMICAL SOC, 2011)
Pt overlayers were deposited on carbon-supported Ir nanoparticles with various coverages. Structural and electrochemical characterizations were performed using transmission electron microscopy (TEM), X-ray diffraction, high-resolution powder diffraction (HRPD), X-ray photoelectron spectroscopy (XPS), X-ray absorption near-edge spectroscopy (XANES), cyclic voltammetry (CV), CO stripping voltammetry, and N2O reduction. The surface of Ir nanoparticles was covered with Pt overlayers with thickness varying from the submonolayer scale to more than two monolayers. Surface analyses such as CV and CO stripping voltammetry indicated that the Pt overlayers were uniformly deposited on the Ir nanoparticles, and the resultant Pt overlayers exhibited gradual changes in surface characteristics, toward the Pt surface as the surface Coverage increased. The distinct CO stripping characteristics and the enhanced Pt utilization,affected, electrocatalytic activities for methanol oxidation. The electrochemical stability of the Pt overlayer was compared with a commercial carbon-supported Pt catalyst by conducting a potential cycling experiment.
Keywords: ZERO TOTAL CHARGE; PLATINUM-MONOLAYER ELECTROCATALYSTS; OXYGEN REDUCTION; AU NANOPARTICLES; CARBON-MONOXIDE; METHANOL; METAL; PT(111); ELECTROOXIDATION; TRANSITION